2017
DOI: 10.1001/jamaoncol.2016.6120
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Capecitabine in Combination With Docetaxel, Epirubicin, and Cyclophosphamide for Early Breast Cancer

Abstract: clinicaltrials.gov Identifier: NCT00114816.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
51
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 30 publications
5
51
1
Order By: Relevance
“…Capecitabine is one of the most widely studied drugs in the neoadjuvant and postoperative adjuvant setting of TNBC. Recently, several randomized clinical trials (RCTs) have evaluated the clinical value of combined treatment with capecitabine for TNBC, but the outcomes of these studies were still controversial [ 14 22 ]. Seven meta-analyses summarizing the role of capecitabine in breast cancer adjuvant and neoadjuvant chemotherapy have been performed, six of which included all subtypes of patients, not just TNBC patients [ 13 , 23 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Capecitabine is one of the most widely studied drugs in the neoadjuvant and postoperative adjuvant setting of TNBC. Recently, several randomized clinical trials (RCTs) have evaluated the clinical value of combined treatment with capecitabine for TNBC, but the outcomes of these studies were still controversial [ 14 22 ]. Seven meta-analyses summarizing the role of capecitabine in breast cancer adjuvant and neoadjuvant chemotherapy have been performed, six of which included all subtypes of patients, not just TNBC patients [ 13 , 23 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Trials investigating newer cytotoxic agents for breast cancer have not yet identified any classes that are clearly superior to taxanes and anthracyclines,2, 3, 4 but the optimal dosage and timing of these two drugs is still unclear. Cell biology and cytokinetic modelling suggest that increasing dose intensity (ie, the amount of drug delivered per unit time) 5 could enhance tumour cell kill, reduce tumour regrowth between cycles, and thereby further improve the likelihood of cure 6, 7.…”
Section: Introductionmentioning
confidence: 99%
“…The FinXX trial, in which 1,500 women in Finland and Sweden were recruited, compared three cycles of docetaxel followed by three cycles of cyclophosphamide, epirubicin, and fluorouracil (T+CEF) and three cycles of docetaxel plus capecitabine followed by three cycles of cyclophosphamide, epirubicin, and capecitabine (TX+CEX); the results showed no significant overall survival impact. However, subgroup analysis clearly indicated a superior benefit of TX+CEX to T+CEF in triple negative (TN) disease [ 1 ]. In the CREATE-X trial using eight cycles of a regimen with 3-week cycles of 2500 mg/m 2 capecitabine, the capecitabine group showed significant survival advantages in relapse-free survival and overall survival compared with the control arm.…”
mentioning
confidence: 99%